"Part of What We Thought and Felt": Antifascism, Antisemitism and Jewish Connections with the New Theatre. (1st May 2021) - Kaiser, Max; Milner, Lisa
Abstract : For much of the twentieth century, the six branches of the New Theatre in Australia presented left-wing theatre within a culture that was largely resistant to their ideas. Their orientation was explicitly pro-working class, their support base including the Communist Party and left-wing trade unions. Like radical theatres in other nations, including the Unity Theatre in Britain, the New Theatre had strong connections to Jewish culture and theatre enterprises, and featured Jewish writers, actors, values and themes. Left-wing, anti-fascist scripts written by Jews in Australia as well as Britain and the USA were often staged. This article discusses the New Theatre's concerns with antisemitism and Jewish politics focussing on selected plays by Laurence Collinson, David Martin and Oriel Gray. These plays provide us with an ideal prism through which to analyse Jewish left-wing and anti-fascist ideas as they were refracted through a transnational left-wing theatre movement.